115k views
8 votes
If f(x) = 3x + 5 and g(x) = -2x - 5x+3, find (f + g)(x).

O A. (f+ g)(x) = -2x + 8
O B. (f + g)(x) = -4x + 8
OC. (f+ g)(x) = -2x2 + 8x+ 8
OD. (f + g)(x) = -2x2 - 2x + 8

User ChuckKelly
by
5.5k points

1 Answer

2 votes

Answer:

D. (f + g)(x) = -2x² - 2x + 8

Explanation:

Given:

  • f(x) = 3x + 5
  • g(x) = -2x² - 5x + 3

Find (f + g)(x):


f(x) + f(g)


3x + 5 + ( -2x^(2) - 5x + 3 )


3x + 5 - 2x^(2) - 5x + 3

Combine like terms:


-2x^(2) + 3x - 5x + 5 + 3


-2x^(2) - 2x + 8

Answer: D. (f + g)(x) = -2x² - 2x + 8

User Hoby
by
4.6k points